Environmental foundations to the rise of early civilisations in China - Zhuang, Yijie (Cambridge elements. Elements in ancient East Asia,, 2024)
The transition from the middle to late Holocene (5000-4000 BP) coincided with profound socioeconomic transformations and intensified regional and trans-regional interactions in late prehistoric China. These environmental and socioeconomic changes gave rise to diverse lifeways and settlement modes that constituted the foundation for the emergence of regional civilisations. In this Element, prehistoric China is divided roughly into the Highlands, Lowlands, and Coastal areas, each with unique environmental and ecological conditions and distinctive technological and economic traditions between 5000-4000 BP. The author gathers and reviews large amounts of environmental and archaeological data, and reconstructs brief environmental and settlement changes and lifeways. The author argues that environmental conditions and subsistence adaptations are two of the engines driving the increased socioeconomic complexity and rise of civilisations in the late prehistoric China. This title is also available as Open Access on Cambridge Core.